INDIKATOR JARAK AMAN MINIMUM MATA TERHADAP MONITOR MENGGUNAKAN SENSOR ULTRASONIK PING))) BERBASIS MIKROKONTROLER AT89S51 - Setiya Purnawan (LPPM Universitas Bina Sarana Informatika, 2010)
Faced with a monitor screen, be it television or computer monitor has becomepublic consumption every day. The behavior needs to be directed so as notaffected by radiation from the monitor. Placing the eye at a safe distance is one of the simplest solution, but it is difficult to do without the indicator. Through the development of a combination of hardware and software-based microcontroller,ultrasonic sensors, seven segment displays, and the buzzer can be assembled asafe distance indicators to monitor eye. The indicator works by detecting the distance, and give warning if the minimum safe distance of the eye with the monitoris not reached. This indicator can help users monitor in determining the proper position to reduce the danger of radiation from the monitor. Keywords: monitor radiation, ultrasonic, microcontroller